Electrosprayed cashew gum microparticles for the encapsulation of highly sensitive bioactive materials. (15th July 2021) - Vázquez-González, Y.; Prieto, C.; Filizoglu, M.F.; Ragazzo-Sánchez, J.A.; Calderón-Santoyo, M.; Furtado, R.F.; Cheng, H.N.; Biswas, A.; Lagaron, J.M.
Graphical abstract: Highlights: Cashew gum microparticles encapsulating β-carotene were produced by electrospraying. Smooth and spherical microparticles with sizes between 3 and 6 μm were obtained. 11 % of extractable β-carotene confirmed the efficiency of the encapsulation process. Cashew gum demonstrated to offer thermoprotection to β-carotene. Photoprotection for β-carotene was observed for short periods of time. Abstract: This study focuses on the production and characterization of electrosprayed cashew gum (CG) microparticles that encapsulate β-carotene. CG is an inexpensive, non-toxic polysaccharide obtained from Anacardium occidentale trees. Encapsulation of β-carotene in CG was performed by electrospraying from two emulsion formulations (water : oil ratios 80:20 and 90:10 (v/v)) in which the dispersed phase consisted of β-carotene dissolved in castor oil, and the continuous phase was a CG aqueous solution. Spherical particles with smooth surface and medium size between 3 and 6 μm were obtained. The particles produced from the 90:10 (v/v) emulsion showed a loading capacity of 0.075 ± 0.006 % and a minor amount of extractable β-carotene, 10.75 ± 2.42 %. ATR-FTIR confirmed the absence of interaction between the particles' components. CG demonstrated to offer thermoprotection, and photoprotection for short periods of time. These results make CG a viable candidate to encapsulate bioactive compounds via electrospraying for agricultural, food and pharmaceutical applications.